Balancing bureaucracy and communal values in diffusing the innovation process : strategic communication challenges from the Malaysian perspectives - Norhafezah Yusof,; Romlah Ramli,; Napat Ruangnapakul, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The transmission of agricultural messages such as innovation in agricultural settings requires good planning from a strategic communication viewpoint. Moreover, there has been a call from various quarters that demand a holistic approach to solve this miscommunication issue. Thus, this study aims to understand the experiences of senior officers who are in charge of managing transmission of agricultural knowledge and training in various agriculturally based organisations. In-depth interviews were conducted with experts representing local and federal research-based and execution agencies. The data were analysed thematically. The interview protocol was developed from a literature review and tested on an expert who was also in the field of agriculture. The findings indicate that the bureaucracy system negates transfer of technology to the recipients, while communal culture presents as stimuli for successful diffusion of innovation. Thus, balancing bureaucracy and communal values offers a positive impact on the transfer of new technology to the recipients. The results offer a new understanding on the complexity of transfer of innovation knowledge and practices in terms of planning and implementing phases faced by the officers. To add, within the context of the study, top-down and bottom-up communication strategies need to be realigned to ensure the sustainability of effective innovation transfer in Malaysia. Future research could address the different scope of communication aspects in these organisations and extend our in-depth interview approach to various officers at national and regional levels.